Highly Pathogenic Avian Influenza (H5N1) in Humans after the emergence of clade 2.3.4.4b in 2020. - Haley Stone; Adriana Notaras; Rosalie Chen; Jared Edgeworth; Ashley Quigley (University of New South Wales, 2023)
The highly pathogenic avian influenza virus A (HPAI) H5N1 was first identified in a farmed goose in 1996 from China. High pathogenic avian influenza viruses cause severe disease in poultry and represent a smaller proportion of avian influenzas. In 2008, the H5Nx acquired the function to reassort its neuraminidase (N) and created the 2.3.4.4 H5Nx clade. Initial outbreaks of 2.3.4.4b began in H5N8 and H5N6 in 2016. However, in 2020, whole genome sequencing (WGS) conducted in the Netherlands detected a new H5N1 clade, 2.3.4.4b in wild birds along the Adriatic flyway, which reassorted from H5N8 2.3.4.4b clade. Currently, the 2.3.4.4b HPAI H5N1 outbreak is the dominant circulating strain in the panzootic outbreak. This clade has been responsible for large outbreaks within avian species and spillover into human cases has occurred. The earliest reported human case was in 2021. The reported human cases of this clade have been within the United Kingdom (UK), the United States (US), China, Spain, Vietnam, Ecuador, and Chile.